L’enseignement à distance aujourd’hui : Renouveau numérique et transmutation du rôle de l’enseignant - ERTEK, BETÜL (My University, 2021)
L’enseignement du numérique intègre nécessairement les technologies de l’information et de la communication pour proposer des moyens d’apprentissage novateurs. L’ajout de nouveaux moyens durant le confinement nous pousse à nous interroger sur la question des innovations dans l’enseignement du numérique et des nombreuses transformations qui en découlent. Un constat peut être établi : le rôle et les tâches traditionnelles de l’enseignant ne sont plus vraiment les mêmes. Plusieurs questions ont été soulevées. Les nouveaux modèles d’apprentissage ont-ils un impact sur le rôle de l’enseignant ? En quoi ces nouveaux modèles d’apprentissage influent sur le travail enseignant ? Quelles sont les nouvelles compétences à mettre en œuvre et à maîtriser afin de répondre aux perspectives éducatives en constante évolution ? Émanera de ce travail une réflexion sur les évolutions de l’enseignement du numérique simultanément aux transmutations du rôle de l’enseignant. Il sera question de mettre en lumière les changements survenus pendant le confinement et d’expliciter les modèles proposés dans le champ de l’éducation avec une volonté d’attirer l’attention sur les évolutions marquantes, notamment dans le rôle des enseignants ainsi que le suivi des dispositifs par la nouvelle technologie numérique au 21e siècle. Cette recherche s’intéresse au développement des TIC (Technologies de l’Information et de la Communication) qui sous-tendent une pédagogie connectiviste en favorisant la naissance d’un nouveau profil d’enseignant ainsi que des transmutations dans son attribution. Pour ce faire, il a été relevé quatre rôles qui identifient l’enseignant d’aujourd’hui ainsi nommés : bricoleur ; collaborateur ; chercheur ; modélisateur. L’interprétation des recherches nous laisse penser que chacun des enseignants peut se situer dans plusieurs rôles : tantôt bricoleur et/ou collaborateur, tantôt chercheur et/ou modélisateur et inversement. Loin du modèle classique d’antan, il est question de mutations mais surtout de transmutations considérables et accélérées du rôle de l’enseignant avec un glissement progressif vers une spécification pédagogico-numérique.

Digital education integrates information and communication technologies to provide innovative learning methods. Introduction of new tools during the pandemic lockdown makes us inquire the question of innovations in digital education and the many resulting changes. We can now express that the teachers’ role and their traditional duties are no longer the same. From this point of view, some questions have been raised: Do new distance education models have an impact on the role of the teacher? How do relevant new distance education models affect teaching? What are the new skills that need to be known and applied in order to respond to the ever-evolving educational methods? This study will include a review of developments in digital education together with the transformations in the teacher’s role. In order to emphasize the changes that occurred during the quarantine and to draw attention to important developments such as the role of teachers and monitoring, the use of technology in the 21st century and the models proposed in the field of education will be explained in our study. The research is concerned with the development of ICT (Information and Communication Technologies) that supports the connectionist pedagogy by encouraging the emergence of a new teacher profile as well as the transformations in its role. To do so, four roles that define today’s teacher are described: organizer; collaborator; researcher; modeler. Based on the research, it is possible to say that each of the teachers can assume multiple roles: sometimes an organizer and/or a collaborator, sometimes a researcher and/or a modeler and vice versa. Unlike the classic model of past, it is a question of transformation/change but above all, it also includes the concern arising from significant and accelerated transformations with the gradual shifting of the teacher’s role towards pedagogical-digital qualification.

Digital education integrates information and communication technologies to provide innovative learning methods. Introduction of new tools during the pandemic lockdown makes us inquire the question of innovations in digital education and the many resulting changes. We can now express that the teachers’ role and their traditional duties are no longer the same. From this point of view, some questions have been raised: Do new distance education models have an impact on the role of the teacher? How do relevant new distance education models affect teaching? What are the new skills that need to be known and applied in order to respond to the ever-evolving educational methods? This study will include a review of developments in digital education together with the transformations in the teacher’s role. In order to emphasize the changes that occurred during the quarantine and to draw attention to important developments such as the role of teachers and monitoring, the use of technology in the 21st century and the models proposed in the field of education will be explained in our study. The research is concerned with the development of ICT (Information and Communication Technologies) that supports the connectionist pedagogy by encouraging the emergence of a new teacher profile as well as the transformations in its role. To do so, four roles that define today’s teacher are described: organizer; collaborator; researcher; modeler. Based on the research, it is possible to say that each of the teachers can assume multiple roles: sometimes an organizer and/or a collaborator, sometimes a researcher and/or a modeler and vice versa. Unlike the classic model of past, it is a question of transformation/change but above all, it also includes the concern arising from significant and accelerated transformations with the gradual shifting of the teacher’s role towards pedagogical-digital qualification
Günümüzde uzaktan eğitim: Dijital yenilenme ile öğretmenin rolünün dönüşümü
Distance education today: Digital renovation and transformation of the teacher’s role
Keywords: Eğitim; Yabancı Diller Eğitimi; Öğretmen Eğitimi; Education; Education in Foreign Languages; Teacher Training; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; distance education; digital education; ICT education; role of the teacher; renovation/transformation; uzaktan eğitim; dijital eğitim; BİT; öğretmenin rolü; yenileme/ dönüşüm; enseignement à distance; enseignement numérique; enseignement des TIC; rôle de l’enseignant; renouveau/transmutation